(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This study focused on the analysis of sugarcane arrears from the year 2006-07 to 2020-21concerning 'The Baghpat co-operative sugar mills Ltd”. The results do not show any particular trend for the arrears in the concerned period, instead, we found sporadic behaviour, the random rise and fall in arrears. The study further identified the responsible factors for such behaviour using multiple linear regression technique. The rate of depreciation, profitability and total income of the mill are found to be the three main factors influencing arrears. The Total factor productivity(TFP) of the mill is also an important reason for the arrears, which is calculated using DEA based Malmquist Productivity Index (MPI). Further, these all factors are studied together using System Dynamic Modelling by Causal Loop Diagram (CLD).The loop revealed that no single factor is solely responsible for arrears, but all the factors taken in the study are related to each other as the cause and effect and together contribute to arrears behaviour.